Analisis Kewenangan Provos Brigade Mobil Kepolisian Daerah Sumatera Utara dalam Penegakan Disiplin Anggota Sesuai Peraturan Kepala Kepolisian Negara Republik Indonesia: Studi Kasus Provos Brigade Mobil Kepolisian Daerah Sumatera Utara - Wendy Usihen; Tri Reni Novita (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Discipline enforcement among members of the Indonesian National Police is essential to maintaining professionalism, integrity, and public trust. Provos serves as an internal supervisory element responsible for monitoring and examining disciplinary violations, including within the Mobile Brigade Corps (Brimob), whose duties involve high operational risk and intensity. This study analyzes the authority of the Brimob Provos of the North Sumatra Regional Police in enforcing discipline, its field implementation, and the supporting and inhibiting factors. The research used empirical legal methods with a juridical-sociological approach, supported by interviews and secondary data from regulations, books, journals, and related documents. The results show that Provos authority has a clear legal basis and is implemented in accordance with Police Chief Regulation Number 2 of 2016. Its implementation includes routine supervision, sudden inspections, preliminary examinations, and preparation of examination reports for Authorized Superiors (Ankum). Minor violations are handled through coaching and reprimands, while serious cases are coordinated with Paminal and Bidpropam. Supporting factors include legal clarity, command support, and internal coordination, while obstacles include limited personnel, operational intensity, inadequate facilities, and resistance to internal supervision.